Analisis Semiotika Ekspresi Wajah di dalam Ayat-ayat Agung al-Qur’an - Hasanuddin Chaer; Abdul Rasyad; Ahmad Sirulhaq (LP2M STIT Palapa Nusantara, 2019)
Semiotics is the study of signs and symbols as elements and analysis of communication systems. Many verses of the Qur'an show aspects of communication between humans and verses of the Qur'an. This article discusses the study of semiotics with a descriptive analysis approach. The purpose of this essay is to analyze facial expressions in the verses of the Great Qur'an that are expressed verbally. This essay uses Peirce's theory of semiotics in analyzing the facial expressions of people in the world and the faces of people in the afterlife.